2012
DOI: 10.1111/j.1477-2574.2012.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Operative procedures for unresectable pancreatic cancer: does operative bypass decrease requirements for postoperative procedures and in-hospital days?

Abstract: In this study, duodenal, biliary and double bypasses in unresectable patients were not associated with fewer invasive procedures following non-therapeutic laparotomy and did not appear to reduce the total number of inpatient hospital days prior to death. Continued effort to identify unresectability prior to operation is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
4
19
0
2
Order By: Relevance
“…6,7,9,10,22 On the other hand, recurrence rate of after endoscopic treatment for malignant BO with duodenal obstruction was 34%. 2 Meta-analyses of studies comparing endoscopy and surgery for malignant BO revealed that recurrence of BO was significantly less in biliary bypass compared to biliary stent.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7,9,10,22 On the other hand, recurrence rate of after endoscopic treatment for malignant BO with duodenal obstruction was 34%. 2 Meta-analyses of studies comparing endoscopy and surgery for malignant BO revealed that recurrence of BO was significantly less in biliary bypass compared to biliary stent.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…24,25 With regards to GOO recurrence, studies showed that incidence rate ranges from 0% to 4.8%. 6,7,9,10,14,15,22 In addition, Hamada et al 2 reported that dysfunction of the duodenal stent was observed in 21% of the patients. Meta-analysis of studies comparing stent and surgery for malignant GOO also revealed that reintervention was less required in gastrojejunostomy compared to stent placement.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 3 more Smart Citations